Gourmet fruits & vegetables carving class: a beautiful learning experience with autism spectrum children / Ahmad Redhuan Abu Bakar … [et al.] - Abu Bakar, Ahmad Redhuan; Johari, Noorsa Riza; Mashuri, Mas Affandy; Zaeimoedin, Teku Zariff (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
On 22nd May 2024, the Faculty Hotel & Tourism Management UiTM Pulau Pinang had an awesome opportunity to collaborate and dive into a beautiful experience in teaching special needs children. Led by Chef Noorsa Riza Johari and supported by program facilitators - Chef Redhuan, Chef Andy Mashuri and Chef Teku Zariff. The successfuI program with Persatuan Tunas Nuraga was held in Sungai Petani at the Tunas Nuraga Centre. Autism Spectrum might not be a common topic among UiTM lecturers who seldomly encounter students with special needs. However, the recent UiTM intake has seen a number of students with special needs as well as Autism Spectrum conditions. Autism spectrum disorder (ASD) presents unique challenges and strengths in learning and daiIy activities for individuals that are affected by it.